2015
DOI: 10.1007/s00706-015-1584-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of 7-deazaguanine- and 7-deazaadenine-modified DNA at the hanging mercury drop electrode

Abstract: DNA modification with synthetic analogs of natural nucleotides and/or their conjugates with external redox active groups is applied in the development of electrochemical DNA sensors or assay for DNA hybridization, SNP typing, DNA damage and so forth. 7-Deazapurines (Pu*) are analogs of natural purine bases in which N7 atom is replaced by CH group. The Pu* bases retain Watson-Crick base pairing of their parent purines (and the ability to form duplex DNA) but are incapable of Hoogsteen pairing (and thus cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…At 37 °C even the natural DNA got partially modified. Increased reactivity of the dA*‐dsDNA at 25 °C, compared to the natural dsDNA, can be attributed to a reduced stability of duplex DNA in which A residues were substituted with A* (in agreement with our recent electrochemical study ). Inspection of the peak potentials resulting from these modification experiments (Table ) brought further support for the conclusion that it is the BA moiety what is preferentially modified in the ds DNA: at all temperatures these samples gave peak α at −0.570–−0.575 V, which is in a perfect agreement with the value obtained for the dA BA TdT tailing product (Table ).…”
Section: Resultssupporting
confidence: 69%
“…At 37 °C even the natural DNA got partially modified. Increased reactivity of the dA*‐dsDNA at 25 °C, compared to the natural dsDNA, can be attributed to a reduced stability of duplex DNA in which A residues were substituted with A* (in agreement with our recent electrochemical study ). Inspection of the peak potentials resulting from these modification experiments (Table ) brought further support for the conclusion that it is the BA moiety what is preferentially modified in the ds DNA: at all temperatures these samples gave peak α at −0.570–−0.575 V, which is in a perfect agreement with the value obtained for the dA BA TdT tailing product (Table ).…”
Section: Resultssupporting
confidence: 69%
“…This fact is utilized, for example, in PCR amplification of G‐rich sequences where the quadruplex formation could affect the amplification process. For analysis of the A 30 +G* tailing reaction products (Figure C and 3D), only oxidation at PGE was used since, with HMDE, G* does not yield any peak analogous to the G HMDE peak, in agreement with absence of the corresponding redox site in G* . Both voltammetric and PAGE analysis showed that, unlike in the case of A 30 +G tailing products, the length of the tailing products grew gradually with the rising dG*TP:primer ratio, with the average tail length much higher than in the case of dGTP, especially for the 20 : 1 and 50 : 1 ratios and the G* OX signal for the 50 : 1 ratio being ∼10‐fold higher than that for the 1 : 1 ratio.…”
Section: Resultsmentioning
confidence: 96%
“…Mercury drop electrode usually shows better performance for electrochemical reduction of a wide range of organic and inorganic species, compared to the other electrodes because of exhibiting considerable overpotential for hydrogen ion reduction [19–21] . However, the toxicity of mercury electrode encourages the researchers to replace it with less toxic amalgam electrodes which are the mixture of metal and mercury [22–25] …”
Section: Introductionmentioning
confidence: 99%